Vpliv vodenja na izobraževanje fizioterapevtov v zdravstvenem domu - Kokollari, Arbulena (Revija za univerzalno odličnost, 2020)
Research Question (RQ): We are interested in whether physiotherapists in the health center are educated, who most often encourage them to educate, what is their main obstacle to education and whether their acquired knowledge in education helps them in the work process. Purpose: The purpose of the research is to determine whether the method of management influences the attitude of physiotherapists' employees towards education and knowledge. Method: An experimental quantitative survey was conducted using primary and secondary data sources. Primary sources were obtained by means of a survey questionnaire, and a descriptive research method was used to obtain secondary sources, in the way of systematic review of Slovenian and foreign literature. Results: We found that physiotherapists are mostly self-motivated to educate themselves. Of all the leaders in the health center, they are most encouraged by the main physical therapist. One of the main obstacles to education was financial resources. Physiotherapists, however, are very happy with the training, as their knowledge of training helps them a lot in the work process. Organization: The results obtained are helpful to all health care managers and other employees in order to describe the current state of management, education and employee satisfaction. By interpreting these, we can see which areas can be further improved for better quality service. Society: Education is of great importance in providing a better quality service and thus improving the outcome of the patient treatment process and thus increasing the efficiency and effectiveness of the institution. Originality: The institute can only develop professionally with the continuous professional and personal development of its employees, which only allows for continuous education and further training and mutual cooperation of employees. The study obtained the first data on the education of physiotherapists at the primary level of health care and the impact of the management method. Limitations/Future Research: Further research could extend the research to a larger sample. In this way, we could also get an overall picture of what kind of attention is being given by
Keywords: barriers to education; education at work; encouragement to education; fizioterapija; guidance; health center; izobraževanje ob delu; ovire za izobraževanje; physiotherapy; spodbujanje k izobraževanju; vodenje; zdravstveni domovi